POLITENESS STRATEGIES IN “INDONESIAN STAND UP COMEDY SEASON I” PERFORMED BY THE WINNER - KURNIAWATI, ANISA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Politeness, Face, FTA (face threathening acts) People in the world cannot live without interaction and communication with someone else because they belong to social community. One of strategy which is used in communication is politeness. This study is about politeness strategy. The meaning of politeness in this study is the act of people to please someone’s feeling or minimize the face threatening acts (FTA). It is important for people to know various standards of politeness as a way to have better communication with other people. Object of the study is Indonesian Stand Up Comedy Season I. Two problems of the study are formulated as follows: (1) What FTA strategies are performed by Ryan in “Indonesian Stand Up Comedy I Season I” ? and (2) What politeness strategies are used by Ryan in “Indonesian Stand Up Comedy I Season I” ?This research uses qualitative approach. The data source is the transcript of Ryan’s utterances in “Indonesian Stand Up Comedy Season I”. In this research,the researcher used document analysis because the data which are analyzed are the utterances containing of FTA and politeness strategies in “Indonesian Stand Up Comedy Season I”.The writer found that Ryan applies FTA strategies containing on record and off record with baldly on record is the most used.In performing FTA, the speaker intended to use strategies which can make audiences laugh. It means that the baldly on-record strategy is the most effective strategy to  make a joke andmake  audience laugh rather than another strategy.The writer suggests to the next researchers to use the other objects which reflect more about the appliance of FTA in daily life to make the readers more understand the concept of performing FTA in real life, especially in analyzing how another stand up comedian apply politeness strategies. The next  researchers can compare the result of their analysis to know whether baldly on-record strategy is the most effective way to make jokes and make audiences laugh or not.